2013
DOI: 10.1093/jnci/djs529
|View full text |Cite
|
Sign up to set email alerts
|

HIV Infection Status, Immunodeficiency, and the Incidence of Non-Melanoma Skin Cancer

Abstract: Background The incidence of non-melanoma skin cancers (NMSCs), including basal cell (BCC) or squamous cell carcinoma (SCC), is not well documented among HIV-positive (HIV(+)) individuals. Methods We identified 6560 HIV(+) and 36 821 HIV-negative (HIV(-)) non-Hispanic white adults who were enrolled and followed up in Kaiser Permanente Northern California from 1996 to 2008. The first biopsy-proven NMSCs diagnosed during follow-up were identified from pathology records. Poisson models estimated rate ratios that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
126
0
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 186 publications
(143 citation statements)
references
References 52 publications
6
126
0
8
Order By: Relevance
“…In general, the presence of chronic immunosuppression has been linked to an increased risk for the development of squamous cell carcinomas (SCC) and to a lesser degree also basal cell carcinomas (BCC) (126)(127)(128)(129)(130). Most studies regarding NMSC in patients on immunosuppression have been reported in solid organ transplant patients.…”
Section: Epidemiology In Ibd Patientsmentioning
confidence: 99%
“…In general, the presence of chronic immunosuppression has been linked to an increased risk for the development of squamous cell carcinomas (SCC) and to a lesser degree also basal cell carcinomas (BCC) (126)(127)(128)(129)(130). Most studies regarding NMSC in patients on immunosuppression have been reported in solid organ transplant patients.…”
Section: Epidemiology In Ibd Patientsmentioning
confidence: 99%
“…Opportunistic infections are the most common manifestation, although sudden progression of existing KS or development of new lesions may also occur [73][74][75][76]. A systematic review identified 54 cohort studies of 13 103 patients starting HAART, of whom 1699 developed IRIS, 6.4% of whom had KS [77].…”
Section: Haartmentioning
confidence: 99%
“…With a follow-up of 28 months, a study presented only in abstract form reported an impressive CR rate and OS of 100% in patients treated with this regimen [74]. The studies performed in patients with BL are summarized in Table 4.7.…”
Section: Burkitt Lymphoma/leukaemiamentioning
confidence: 99%
See 1 more Smart Citation
“…[9] Two studies indicate that HIV-positive white individuals have a higher incidence of SCC than HIV-negative individuals. [10,11] HIV is therefore likely to have an impact on the age dependence of SCC in SA, regardless of population group.…”
Section: Researchmentioning
confidence: 99%